BIOCHEMICAL CHANGES IN RESPONSE TO SALINITY IN CHICKPEA (CICER ARIETINUM L.) DURING EARLY STAGES OF SEEDLING GROWTH - M. Arefian; S. Vessal; A. Bagheri (Journal of Animal and Plant Sciences, 2014)
Salinity is a serious abiotic stress, causing oxidative stress. Various biochemical parameters in chickpea genotypes were considered under varied NaCl concentrations (0, 8 and 12 dS.m-1 ( . This experiment was done as factorial arrangement (genotype × salt concentration × time) in a completely randomized design. Samples were collected at 21 and 28-day old seedlings (28-DOS). The results revealed that increasing salt concentration resulted in higher levels for malondialdehyde content; among genotypes, MCC806 with 2.2 and MCC760 with 0.7 had the highest and lowest amount, respectively. Proline and protein contents were significantly higher in MCC544 by 27-fold increase (for proline) and 30% (for protein) relative to control in 28 DAS at 12 dS.m-1 of salt. The leaf soluble carbohydrates also increased significantly in MCC544 and MCC760 compared with the others. The minimum decline of electrolyte leakages (6%) was belonged to MCC760 while MCC806 genotypes showed the highest decrease rate (more than 20%). Total leaf chlorophyll content decreased in all genotypes during the stress. However, morphological damages in MCC544 and MCC760 genotypes were less in 28-DOS at 8 and 12 dS.m-1 NaCl, respectively. Overall, proline and leaf soluble carbohydrates were more consistent with salt tolerance responses of the genotypes, and 2 weeks after stress initiation (28-DOS) could be a critical stage for screening the genotypes.
Keywords: Chickpea; Proline; Salinity; Total chlorophyll; Total soluble protein